MODEL POLICY DESIGN FOR THE BEEF CATTLE DEVELOPMENT IN SOUTH SULAWESI - Machmud Achmad; Sri Hartoyo; Bustanul Arifin; Muhammad Said Didu (Journal of Management and Business Review, 2014)
This study examines some factors that influence policies on developing cattle beef and designing integrated planning systems in South Sulawesi. The method for this study includes qualitative and quantitative approaches using survey method to obtain primary data. Data were analysed and presented in the form of descriptive tables and graphs with analytical tools policy. Results were obtained from choices of recommendations which are elaborated in the form of strategy and policy implications based on expert opinions (expert judgment). Internal and External Matrices were generated by the SWOT analysis and the QSPM. The results show that current position of beef cattle in South Sulawesi is in the quadrant of growth and development. Analysing all the factors from SWOT approach, four strategies were developed to determine the beef cattle policy strategy. Using the QSPM, the results further suggest that the best strategy is priority strategy as seen from its QSPM value of 6,901.An integrated system between the beef cattle rancher and crop (rice and corn), implies that in order to achieve this goal, technology improvement and innovation play important roles, especially technology for the feed processing system.